Subaltern Silence and the Politics of Agency in Midnight’s Children (Siddhajyoti Interdisciplinary Journal, 2026)
This paper critically examines the representation of subaltern women and their agency in Salman Rushdie’s Midnight’s Children. It particularly argues that Rushdie’s female characters embody subalternity, with their identities and social positions shaped by the intersecting forces of colonialism and patriarchy in postcolonial India. At the same time, these characters exercise strategic forms of agency within hegemonic discourses structured by colonial, patriarchal, and capitalist frameworks. Through a close textual reading, the paper explores how Rushdie articulates both the silencing and the emergence of marginalized voices, suggesting that silence itself can function as a mode of resistance to patriarchal ideology. The analysis engages with Gayatri Chakravorty Spivak’s postcolonial theory of subalternity and Laura M. Ahearn’s concept of agency to illuminate the nuanced ways in which Rushdie’s women navigate multiple layers of oppression in textual analysis process. Finally, the study reveals that while the female characters are silenced by imperial and patriarchal systems, they simultaneously enact distinct, context-dependent forms of agency within dominant power structures. It concludes that the politics of agency in Midnight’s Children is not fixed but fluid, operating within and against the very systems it contests.